(untitled) (Revista Contexto & Educação, 2026)
The main objective of this article is to analyze the age-grade distortion rates and school performance indicators, such as grade repetition, dropout, and evasion, in the municipal area of ​​the city of Santa Maria/RS, in addition to suggesting possible strategies to address school failure. The data used were obtained from a survey conducted in the Master’s Course of the Postgraduate Program in Public Policies and Educational Management at the Federal University of Santa Maria. The research was based on a qualitative approach (Minayo, 2010; Flick, 2013) and used the case study method (Yin, 2011), with the municipal public education network of Santa Maria/RS as the field of analysis. To collect information, data from the School Census were used, in addition to semi-structured interviews and online questionnaires applied to managers of the Municipal Department of Education and municipal schools. The results indicate that age-grade distortion in Elementary Education is a complex phenomenon, associated with factors such as public policies, family culture, social vulnerability, and specific personal situations. It is concluded that the topic still offers ample possibilities for more in-depth and specific investigations, such as, for example, listening to students and/or family members in situations of age-grade distortion, exploring their perceptions about education, their life plans, among other aspects.